Roles of Crop Boom (Orange) in Biodiversity Conservation in the Northern Limestone Mountain Region of Vietnam - Dung, Ngo Ngoc; Toan, Le Trong; Chi Trung, Tran; Thi Vinh, Nguyen; Thi Van Hue, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4DO - 10.25073/2588-1094/vnuees.4669, 2021)
This study examines the roles of crop boom (orange) in biodiversity conservation in Cham Chu Nature Reserve, Tuyen Quang province in the Northern Limestone Mountain Region of Vietnam. The results indicatedthat the local policy on orange development in Tuyen Quang since 2000 has made positive contributions to both local livelihood improvements and biodiversity conservation. On average, household income has significantly increased (VND 161 million Vietnam/household/year), of which income from sale of oranges made up 62% of the total household income. Poverty rate has been reduced by half during the last 10 years. Therefore, the dependence of the local livelihoods on the harvesting of forest resources has remarkably decreased, accounting for only 1% of the total household income. Data analysis indicates that the trend of increasing orange area (from 7% in 1986 to 27% in 2017) is related to the increasing forest cover in Cham Chu Nature Reserve (60.4 % of 1986 to 63.8% in 2017) and the decreasing trend of forested areas under human impact (11.3% in 2007 to 3.7% in 2017). Notably, the number of cases of violation of the Law on Forest Protection and Development has significantly decreased (from 66 in 2013 to 13 cases in 2017) in the study area. The case of Phu Luu shows that commodity agricultural development has had a positive impact on biodiversity conservation at the local level. Recommendations are provided at the end of the paper as how to strengthen thelinkages between commodity agriculture and biodiversity conservation in the limestone mountains of Northern Vietnam so that growth of rural incomes, poverty reduction, and biodiversity conservation can all take place.